Pear genomes display significant genetic diversity and provide novel insights into the fruit quality traits differentiation - Baopeng Ding; Haifei Hu; Yunpeng Cao; Ruirui Xu; Yujing Lin; Tahir ul Qamar Muhammad; Yuqin Song; Guangqi He; Youzhi Han; Huangping Guo; Jun Qiao; Jianguo Zhao; et al. (Horticultural Plant Journal)
The pear (Pyrus spp.) is well known for diverse flavors, textures, and global horticultural importance. However, the genetic diversity responsible for its extensive phenotypic variations remains largely unexplored. Here, we de novo assembled and annotated the genomes of the maternal (PsbM) and paternal (PsbF) lines of the hybrid ‘Yuluxiang’ pear and constructed the pear pangenome of 1.15 Gb by combining these two genomes with five previously published pear genomes representing cultivated and wild germplasm. Using the constructed pangenome, we identified 21 224 gene PAVs (Presence-absence variation) and 1 158 812 SNPs (Single Nucleotide Polymorphism) in the non-reference genome that were absent in the PsbM reference genome. Compared with SNP markers, PAV-based analysis provides additional insights into the pear population structure. In addition, some genes associated with pear fruit quality traits have differential occurrence frequencies and differential gene expression between Asian and European populations. Moreover, our analysis of the pear pangenome revealed a mutated SNP and an insertion in the promoter region of the gene PsbMGH3.1 potentially enhance sepal shedding in ‘Xuehuali’ which is vital for pear quality. PsbMGH3.1 may play a role in the IAA pathway, contributing to a distinct low-auxin phenotype observed in plants by heterologously overexpressing this gene. This research helps capture the genetic diversity of pear populations and provides genomic resources for accelerating breeding.